2022
DOI: 10.1038/s41598-022-17854-0
|View full text |Cite
|
Sign up to set email alerts
|

Biological and chemical properties of five mineral oxides and of mineral trioxide aggregate repair high plasticity: an in vitro study

Abstract: Calcium silicate-based cements have diverse applications in endodontics. This study aimed to evaluate the antibiofilm action, biocompatibility, morphological structure, chemical composition and radiopacity of Five Mineral Oxides (5MO), Mineral Trioxide Aggregate Repair High Plasticity (MTA Repair HP), and Mineral Trioxide Aggregate (MTA) cements. MTT analysis was used to test the antibiofilm action of these cements against five anaerobic microorganisms, and test their biocompatibility with mouse macrophage (RA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 39 publications
(47 reference statements)
0
10
0
Order By: Relevance
“…MMC values were determined, and 10 µL of MIC and a concentration above and below MIC were seeded in Brucella agar. After incubation (48 h/37 °C), MMC corresponded to the well with no grown bacteria and with the lowest concentration of BGP-AqExt [ 4 , 41 ].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…MMC values were determined, and 10 µL of MIC and a concentration above and below MIC were seeded in Brucella agar. After incubation (48 h/37 °C), MMC corresponded to the well with no grown bacteria and with the lowest concentration of BGP-AqExt [ 4 , 41 ].…”
Section: Methodsmentioning
confidence: 99%
“…Immediately after, the microplates were incubated for 10 min at 37 °C and then were agitated in vortex for additional 10 min at room temperature. Finally, a spectrophotometer (Bio-Tek Instruments, Winooski, VT, USA) was used to measure the absorbance of the wells at 570 nm, and data generated were converted to cell viability percentage [ 41 ].…”
Section: Methodsmentioning
confidence: 99%
“…Mineral Trioxide Aggregate material with very high plasticity (MTA Repair HP) has been recently launched, representing a calcium silicate-based cement with enhanced physical and mechanical properties. It is highly biocompatible with human pulp stem cells and with a proven bio-mineralization and antimicrobial activity [80,81].…”
Section: B Mineral Trioxide Aggregatementioning
confidence: 99%
“…Due to its excellent chemical, physical and biological properties, in particular its biocompatibility and osteoconductive potential, it has been used in dentistry for over 20 years [ 10 , 11 , 14 , 15 , 16 , 17 , 18 ]. MTA is used in endodontic treatments [ 13 , 19 , 20 ] and is also recommended in vital pulp therapy to preserve the vitality of dental pulp [ 13 , 19 , 20 ]. Several studies have demonstrated the antibacterial and antifungal properties of this material [ 19 , 20 , 21 , 22 ].…”
Section: Introductionmentioning
confidence: 99%
“…MTA is used in endodontic treatments [ 13 , 19 , 20 ] and is also recommended in vital pulp therapy to preserve the vitality of dental pulp [ 13 , 19 , 20 ]. Several studies have demonstrated the antibacterial and antifungal properties of this material [ 19 , 20 , 21 , 22 ]. Despite the potential of MTA as an antibacterial agent, there are no studies on its use in implantology [ 23 ].…”
Section: Introductionmentioning
confidence: 99%